How can we determine the best neoadjuvant chemoradiotherapy regimen for rectal cancer?. (February 2015) - Jones, Rob Glynne; Tan, David
SUMMARY : The current management of patients with clinically defined 'locally advanced rectal cancer' often involves fluoropyrimidine-based preoperative chemoradiotherapy (CRT) followed by total mesorectal excision. The focus remains primarily on reducing local recurrence, and improving survival, with organ preservation an increasing target. The best neoadjuvant CRT is the most effective regimen, balanced against the tolerability and late functional consequences, which should be selected for the individual according to their individual risk of local and distant recurrence. Hence, what makes the best neoadjuvant treatment depends on the activity and toxicity of the particular schedule, the aims of treatment, the individual disease characteristics and the individual patient pharmacogenomics. Current research efforts focus on enhancing the efficacy of CRT by integrating additional cytotoxics and biologically targeted agents.